A new technique to test the effect of cognition on standing balance in Parkinson's disease - Mayank Bhatt; Bhuvan Mahana; Jonathan J Marotta; Ji Hyun Ko; Douglas Everett Hobson; Tony Szturm (Open Journal of Parkinson's Disease and Treatment - Peertechz Publications, 2019)
Objectives: (a) To determine test-retest reliability of Game Assisted Rehabilitation System (GRS) for standing balance assessment during Single Task (ST) and Dual Task (DT) conditions in people with Parkinson Disease (PD). (b) To examine the discriminant validity of the GRS to evaluate the potential interaction effect of visuomotor and cognitive loads on standing balance in people with PD. Design: The DT effect of a computer based Game-Assisted Rehabilitation System (GRS) on standing balance activities (DT) was evaluated in 30 individuals with PD (Hoehn and Yahr scale stage 2 and 3). Participants performed a series of game-based visuomotor cognitive tasks and head tracking while standing on sponge surfaces. Testing was conducted on two occasions spaced one week apart.